Flat-gain single-stage amplifier using high concentration erbium doped fibers in single-pass and double-pass configurations - Hamida, Belal Ahmed; Latiff, Anas Abdul; Cheng, X. S.; Ismail, Mohammad Afiq; Naji, Ahmed Wathik; Khan, Sheroz; Al-Khateeb, Wajdi Fawzi Mohammed; Ahmed, Hassan Yousif; Harun, Sulaiman Wadi (IEEE Photonics Society, 2012)
A flat gain Erbium-doped fiber amplifier (EDFA) is demonstrated using a gain media of high concentration Silica-based erbium doped fiber (EDF). The amplifier has one stage comprising a 1.5 m and 9 m long EDF optimized for C-band and L-band operations respectively, in a single-pass and double-pass configuration. The CFBG is used at the end of EDF to allow a double propagation of signal and thus increases the attainable gain in both C- and L-band spectra. At input signal power of -30 dB, the averaged flat gain of approximately 25 dB over C-band region and the averaged flat gain of approximately 30 dB over L-band region are achieved by the double-pass amplifier with gain variation approximately ±3 dB. The corresponding noise figure is maintained at 5 dB with noise figure variation ±0.5 dB.